2022
DOI: 10.3390/antiox11102010
|View full text |Cite
|
Sign up to set email alerts
|

Exogenously-Sourced Salicylic Acid Imparts Resilience towards Arsenic Stress by Modulating Photosynthesis, Antioxidant Potential and Arsenic Sequestration in Brassica napus Plants

Abstract: In the current study, salicylic acid (SA) assesses the physiological and biochemical responses in overcoming the potential deleterious impacts of arsenic (As) on Brassica napus cultivar Neelam. The toxicity caused by As significantly reduced the observed growth and photosynthetic attributes and accelerated the reactive oxygen species (ROS). Plants subjected to As stress revealed a significant (p ≤ 0.05) reduction in the plant growth and photosynthetic parameters, which accounts for decreased carbon (C) and sul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(5 citation statements)
references
References 81 publications
0
5
0
Order By: Relevance
“…SA is a signaling molecule involved in various stress responses, including biotic and abiotic stressors [ 41 ]. Additionally, it has been reported to induce the expression of antioxidant enzymes and increase the production of non-enzymatic antioxidants, thereby contributing to ROS detoxification in plants [ 46 ]. The results of this study align with previous research that reported a positive effect of SA on the antioxidant defense systems of plants [ 47 ].…”
Section: Discussionmentioning
confidence: 99%
“…SA is a signaling molecule involved in various stress responses, including biotic and abiotic stressors [ 41 ]. Additionally, it has been reported to induce the expression of antioxidant enzymes and increase the production of non-enzymatic antioxidants, thereby contributing to ROS detoxification in plants [ 46 ]. The results of this study align with previous research that reported a positive effect of SA on the antioxidant defense systems of plants [ 47 ].…”
Section: Discussionmentioning
confidence: 99%
“…The most common method to obtain salicylic acid is chemical synthesis from phenol by the Kolbe-Schmitt reaction discovered in 1859. The substrate of this reaction is sodium phenolate, the main product is sodium salicylate and the final product is salicylic acid This method enables the production of this acid on a industrial scale [1,2]. As reported in the literature, salicylic acid has also been synthesised from natural wintergreen oil according to the principles of so-called 'green chemistry' [4].…”
Section: Chemical Structurementioning
confidence: 99%
“…superoxide dismutase (SOD), ascorbate peroxidase (APX) and glutathione reductase (GR), as well as non-enzymatic antioxidants such as gluta thione and acetylsalicylic acid. It also influences the regulation of sulphur uptake, thus affecting the synthesis of cysteine, methionine, heavy metal chelates, coenzymes, and vitamins [1,2].…”
Section: Introductionmentioning
confidence: 99%
“…Salicylic acid (SA), a key regulator of redox signaling and plant immunity, has been observed in the realm of plant stress management and sustainable agro-ecology and food systems [18]. Bano et al [19] revealed that SA application in response to As stress modulates the activities of antioxidant enzymes involved in the N metabolic pathways and impacts the signaling of the NO 3 − uptake system. SA is recommended for improving the capacity of plants to withstand abiotic stress by promoting growth and enhancing photosynthetic efficiency [20].…”
Section: Introductionmentioning
confidence: 99%